THE INFLUENCE OF REVEALED COMPARATIVE ADVANTAGE (RCA) INDEX, INDIA’S GDP, AND INDIA PALM OIL CONSUMPTION TOWARD CRUDE PALM OIL EXPORT VOLUME TO INDIA ( 2000 – 2014 ) - Yolanda Nerissa Arviana; Dody Setyadi; Agus Suratno (JOBS (Jurnal Of Business Studies), 2016)
This research aims to analyze the influence of RCA Index, India’s GDP, and India Palm Oil Consumption toward Crude Palm Oil Export to India. The data that were used was secondary data during period 2000 – 2014, which were analyzed using multiple regression analysis to estimate the influential factors, and RCA Formula were used to determine the comparative advantage of the Indonesian crude palm oil in international market. According to data analysis report it shows that RCA Index, India’s GDP, and India Palm Oil Consumption simultaneously had significant influence toward Crude Palm Oil export to India. Nevertheless, partially only RCA Index and India’s GDP that has significant influence toward Crude Palm Oil export to India. While the Determination Coefficient (Adjusted R2) = 0.913 or 91.3%, it means that the Crude Palm Oil Export (variation) to India was 91.3% which was explained by RCA Index, India’s GDP, and India Palm Oil Consumption, and the rest of 8.7% were affected by any other factors outside the models, such as Interest Rate, Crude Palm Oil Domestic Consumption, Indonesia’s GDP, etc.